Ignition and combustion characteristics of coal-water-oil slurry placed on modified metal surface at mixed heat transfer - Feoktistov D. V. Dmitriy Vladimirovich; Glushkov D. O. Dmitry Olegovich; Kuznetsov G. V. Geny Vladimirovich; Nikitin D. S. Dmitry Sergeevich; Orlova E. G. Evgeniya Georgievna; Paushkina K. K. Kristina Konstantinovna (2022, 2022)
Title screen